eifj fjei =δijhi, hihj = hjhi,
hiej ejhi =


(i = j)
−ej (i j = ±1)
0 (otherwise)
hifj fjhi =


(i = j)
fj (i j = ±1)
0 (otherwise)
2eiejei + ejei
= 0 (i j = ±1), eiej = ejei (otherwise),
2fifjfi +
= 0 (i j = ±1), fifj = fjfi (otherwise).
Proof. We define elements Lij U (i = j) by induction on |j i|:
Li,i+1 = ei, Lij = [Lik, Lkj] (i k j),
Li+1,i = fi, Lij = [Lik, Lkj] (i k j).
For a, b U, [a, b] is ab ba by definition.
Assertion 1 The Lij are well-defined.
We prove this by induction on N = |j −i|. Since the proof for i j is the same
as the proof for i j, we prove it only for i j. Assume that it is already proved
up to N 1. We shall show for 1 l N 2 that
[Li,i+l+1, Li+l+1,i+N ] = [Li,i+l, Li+l,i+N ] . (2.1)
Since we have Li,i+l+1 = [Li,i+l, ei+l] by the induction hypothesis, the left hand
side of (2.1) equals [[Li,i+l, ei+l] , Li+l+1,i+N ], which is the same as
[ei+l, [Li,i+l, Li+l+1,i+N ]] + [Li,i+l, [ei+l, Li+l+1,i+N ]] .
We now notice that Li,i+l and Li+l+1,i+N are non-commutative polynomials in
ei,...,ei+l−1 and ei+l+1,...,ei+N−1 respectively. Hence the first term is 0. The
second term equals the right hand side of (2.1) by the induction hypothesis.
Assertion 2 The Lie algebra g is an irreducible U-module via the following action:
ei ad(Ei,i+1), fi ad(Ei+1,i), hi ad(Eii Ei+1,i+1),
for 1 i n 1. (Recall that the Eij are matrix units.)
To prove that this defines an action of U, we check that ad(Ei,i+1), ad(Ei+1,i)
and ad(Eii −Ei+1,i+1), for 1 i n−1, satisfy the defining relations of U. By the
Jacobi identity, it is enough to see that Ei,i+1,Ei+1,i and Eii Ei+1,i+1 satisfy the
relations, but this is easily checked by direct computation. We remark here that
we also have seen that Lij ad(Eij).
Next we show that g is irreducible as a U-module. Let a be a non-zero U-
submodule of g. It is easy to see that a is not contained in h and that a has
a simultaneous eigenspace decomposition with respect to ad(h). So a contains a
matrix unit Ekl (k = l). We shall show that a contains all Eij (i = j). If i = k and
j = l, then Eij = ad(Eik)Ekl a. If i = k and j = l, then Eij = −ad(Elj)Ekl a.
If i = k and j = l, we consider ad(Eik)ad(Elj)Ekl and we have that Eij is in the
Previous Page Next Page